Serological reactivity and bacterial genotypes in Chlamydia trachomatis urogenital infections in Guadeloupe, French West Indies. Issue 2 (22nd October 2009) - Weill, François-Xavier; Le Hello, Simon; Clerc, Maithé; Scribans, Cédric; de Barbeyrac, Bertille
Abstract : Objectives: To determine the prevalence and genotypes of Chlamydia trachomatis urogenital infection in Guadeloupe, French West Indies, and to compare C trachomatis direct detection to serological testing. Methods: From March to November 2000, 971 consecutive patients (888 women and 83 men) who had been referred to the clinical laboratory of the Institut Pasteur de la Guadeloupe for routine testing for genital infection were recruited. Samples were subjected to a nucleic acid amplification assay (AMP CT, Gen-Probe, San Diego, California, USA). Genotypes were determined by omp1 PCR-restriction fragment length polymorphism analysis. Serological testing was carried out with the commercially available peptide-based ELISA assay (SERO-CT IgG/IgA, Savyon/BMD, Marne-La-Vallée, France). Results: Positive AMP CT test results were obtained for 102 (10.5%) of the 971 samples. The prevalence of infection was 16.9% in men and 9.8% in women. The most common genotypes were E (34.3%), F (23.9%), Da (13.4%), I (9%) and Ia (7.5%). No relationship was found between genogroups and age, sex or clinical symptoms. With AMP CT used as a reference, the sensitivity, specificity, positive and negative predictive values of SERO-CT were 81.1%, 56%, 34.5% and 91.2%, respectively, for IgG and 55.4%, 76.8%, 59.4% and 85.8%, respectively, for IgA. IgG seroprevalence rates were very low (1/5, 20%) in patients infected with genotype Ia strains. Conclusions: The prevalence found in Guadeloupe did not differ significantly from that found in mainland France. The genotypes Da, F, I and Ia were more prevalent in Guadeloupe; however, the SERO-CT assay was unable to detect serum antibodies in 80% of the patients infected with genotype Ia strains.